الفروع التطبيقية المعاصرة لحفظ المال العام في الفقه الإسلامي - العقلا، غادة بنت محمد بن علي (الجامعة الإسلامية بالمدينة المنورة, 2022)
يعد المال العام من أهم المواضيع وأبرزها في العصر الحديث، وقد جاء هذا البحث من أجل دراسة هذا الموضوع المهم من خلال بيان أهمية للمال في الحياة البشرية؛ والحفاظ على المال العام من أهم المسائل التي يجب التنبيه إليها؛ نظرا لغفلة كثير من الناس عنه بسبب انشغالهم بالحفاظ على أموالهم الخاصة، وحصر اهتماماتهم فيه، مع أن الأخير فرع عن الأول؛ فالحفاظ على المال العام حفاظ على الخاص بالتسلسل المنطقي، وقد خلص البحث في نهايته إلى نتائج من أهمها: أن الشريعة حرمت الاعتداء على الأموال عموما وعلى المال العام بخصوصه، وأن ولي الأمر يملك حق تقييد الانتفاع بالمال العام، حسب ما تقتضيه المصلحة العامة، مع التوصية: ضرورة نشر التوعية الإعلامية بمخاطر الاعتداء على المال العام، وعقد الندوات والمؤتمرات والدراسات التي تتناول هذه المخاطر وكيفية الحماية منها والقضاء عليها. Public money is one of the most important and prominent topics in the modern era. This research aims to study this important topic by explaining the importance of money in human life; Preserving public money is one of the most important issues that must be taken into account; this is due to many people neglect about it because of their preoccupation with preserving their own money, and limiting their interests about it, even though the latter is a branch of the former; Preserving public money is to preserve the private in a logical sequence, the research concluded with some findings, the most important of which are: Sharia forbids assaulting money in general and public money in particular, the guardian has the right to restrict the use of public money, as required by the public interest. In the recommendation with the necessity of spreading media awareness of the dangers of assaulting public funds, and holding seminars, conferences and studies that address these risks, how to defend and eliminate them.
Keywords: الفقه الإسلامي -- المال العام -- المعاملات المالية -- المخاطر المالية